If the first equation is multiplied by 3 and then the equations are added, the result is _____.

3x + y = 3
x - 3y = -2

10x = 11
10x = 7
8x = 7

Respuesta :

10x=7
x=7/10, you could work backwards to find y if it asked

Answer:  The correct option is (B) [tex]10x=7.[/tex]

Step-by-step explanation:  The given equations are :

[tex]3x+y=3~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\x-3y=-2~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]

We are to select the correct result if the first equation is multiplied by 3 and then added to the second equation.

Now, multiplying equation (i) by 3, we get

[tex]3(3x+y)=3\times 3\\\\\Rightarrow 9x+3y=9~~~~~~~~~~~~~~~~~~~~(iii)[/tex]

adding equation (iii) to equation (ii), we get

[tex](9x+3y)+(x-3y)=9+(-2)\\\\\Rightarrow 9x+3y+x-3y=9-2\\\\\Rightarrow 10x=7.[/tex]

Thus, the required result is [tex]10x=7.[/tex]

Option (B) is CORRECT.